Grace - Casanova, Mary; Davis, Sarah 1971- (Middleton, WI : American Girl, 2015)
Nine-year-old Grace likes having a plan but she must find a way to be flexible and open to new ideas when she goes to Paris with her mother and has trouble getting along with her cousin, while at home her friends start the business she proposed without her.
8+.
Accelerated Reader AR
Keywords: JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Cooking & Food